Orbits of homogeneous polynomials on Banach spaces - Cardeccia, Rodrigo Alejandro (2021)
We study the dynamics induced by homogeneous polynomials on Banach spaces. It is known that no homogeneous polynomial defined on a Banach space can have a dense orbit. We show a simple and natural example of a homogeneous polynomial with an orbit that is at the same time-dense (the orbit meets every ball of radius), weakly dense and such that is dense for every that either is unbounded or has 0 as an accumulation point. Moreover, we generalize the construction to arbitrary infinite-dimensional separable Banach spaces. To prove this, we study Julia sets of homogeneous polynomials on Banach spaces.